Reinterpreting the Keynesian and Neoclassical Growth Models in Zimbabwe: The History of Eonomic Thought in Perspective: Array - Mukoka, Shame (EuroEconomica, 2022)
This study sought to reinterpret the Keynesians and Neoclassical growth models in the Zimbabwe context. The study adopted an Error Correction Model for estimating annual time series data for the period 1990 to 2020. Out of the five growth models examined, the results of the study confirmed a positive relationship between real GDP and the Harrod-Domar, Solow, Schumpeter and Nurkse growth models, with Lewis growth model exhibiting an inverse relationship, contrary to the positive relationship that underpins the model. The study, recommend the need for the government of Zimbabwe to come up with policies that enhances the attraction of Foreign Direct Investment which could enhance the growth of fixed capital formation. There is also need for revitalization of the industrial sector given that it is operating below capacity as suggested by the study results. The government of Zimbabwe should continue supporting the agricultural sector through its Command agricultural and Pfumvudza initiatives as this would spur agricultural exports, which are key for growth. The government of Zimbabwe should also come up with initiates that enhances innovation, through making budgets for research and development, and enacting laws that govern patents.